1997
DOI: 10.1073/pnas.94.8.4205
|View full text |Cite
|
Sign up to set email alerts
|

Adult fast myosin pattern and Ca 2+ -induced slow myosin pattern in primary skeletal muscle culture

Abstract: A primary muscle cell culture derived from newborn rabbit muscle and growing on microcarriers in suspension was established. When cultured for several weeks, the myotubes in this model develop the completely adult pattern of fast myosin light and heavy chains. When Ca 2؉ ionophore is added to the culture medium on day 11, raising intracellular [Ca 2؉ ] about 10-fold, the myotubes develop to exhibit properties of an adult slow muscle by day 30, expressing slow myosin light as well as heavy chains, elevated citr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
77
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 31 publications
5
77
0
Order By: Relevance
“…In rodent muscles, values close to 50 -60 nM have been reported in slow fibers versus 30 nM in fast fibers. The influence of resting calcium concentration on the determination and maintenance of fiber phenotype has been first hypothesized by Sreter (757), and experiments on rabbit myotube cultures (443) have confirmed the hypothesis showing that the increase of resting calcium concentration induced by a calcium ionophore is followed by a fast-to-slow transformation (see sect. VII).…”
Section: Resting Calcium and Calcium Transientssupporting
confidence: 48%
“…In rodent muscles, values close to 50 -60 nM have been reported in slow fibers versus 30 nM in fast fibers. The influence of resting calcium concentration on the determination and maintenance of fiber phenotype has been first hypothesized by Sreter (757), and experiments on rabbit myotube cultures (443) have confirmed the hypothesis showing that the increase of resting calcium concentration induced by a calcium ionophore is followed by a fast-to-slow transformation (see sect. VII).…”
Section: Resting Calcium and Calcium Transientssupporting
confidence: 48%
“…Kubis et al (27) showed that a modest but sustained rise in [Ca 2ϩ ] i levels induced by 400 nM of the Ca 2ϩ ionophore A-23187 caused marked fast-to-slow fiber type conversion in a rabbit primary skeletal muscle cell culture. This crucial study not only emphasized the importance of [Ca 2ϩ ] i for phenotypic adaptations in mammalian skeletal muscle but also provided an easy method by which to induce fast-to-slow fiber type conversion in muscle cell cultures.…”
Section: A-23187 Treatment Causes Fast-to-slow Fiber Type Conversionmentioning
confidence: 99%
“…However, changes in intracellular free Ca 2ϩ concentration ([Ca 2ϩ ] i ) seem to be essentially involved. Importantly, Kubis et al (27) showed that a modest but sustained rise in [Ca 2ϩ ] i caused by low concentrations of the Ca 2ϩ ionophore A-23187 in the culture medium induced fast-to-slow fiber type conversion in a rabbit primary skeletal muscle cell culture. This clearly emphasizes the importance of Ca 2ϩ for phenotypic adaptations in skeletal muscle.…”
mentioning
confidence: 99%
“…Fiber type shifts are also observed during aging and disease. The importance of changes in intracellular Ca 2ϩ as a trigger for fiber type transformation has clearly been demonstrated by a Ca 2ϩ -ionophore-induced fast-to-slow transformation in primary skeletal muscle cells (4,5). The involvement of calcineurin, a Ca 2ϩ -calmodulin-regulated serine/threonine phosphatase, in transducing the Ca 2ϩ -signal into altered gene expression in skeletal muscle has been established (6,7).…”
mentioning
confidence: 99%
“…We used myotubes of the C2C12 cell line and of a rabbit primary skeletal muscle cell culture that has been shown previously to develop exclusively adult MyHC isoforms (4,5). We provide evidence that inhibition of p38␣/␤ MAPKs resulted in the down-regulation of fast adult MyHCIId/x gene activity.…”
mentioning
confidence: 99%